From cocoon to clinic: The journey of sericin from waste to value in tissue engineering, regenerative medicine, nanomedicine, and anti-infective applications - Ziksahna, Kaan; Arslan, Halil Ibrahim; Adiyil, Rumeysa; Ihlamur, Murat (ELSEVIER, 2026)
Silk sericin, a natural glycoprotein derived from Bombyx mori cocoons, constitutes about 25-30% of the cocoon weight and has recently gained increasing attention as a multifunctional biomaterial. Depending on extraction conditions, reported sericin recovery often falls in the range of similar to 20-30%, while its molecular weight distribution may vary broadly from low-kDa fragments to >200 kDa, which directly influences bioactivity and processability. Its inherent biocompatibility, biodegradability, and low toxicity, combined with antioxidant, anti-inflammatory, antibacterial, and mitogenic properties, make sericin highly suitable for diverse biomedical applications. Sericin has demonstrated remarkable potential in promoting wound healing, bone regeneration, and tissue repair by enhancing fibroblast and keratinocyte proliferation and supporting hydroxyapatite nucleation. These biological activities, together with its ability to modulate inflammatory pathways and oxidative stress, position sericin as a promising candidate in regenerative medicine. In materials science, sericin can be processed into versatile forms such as films, sponges, hydrogels, nanofibers, and membranes. Through crosslinking or blending with natural and synthetic polymers, its structural and mechanical properties can be further optimized. Beyond structural applications, sericin's amphiphilic nature enables it to act as a carrier for both hydrophobic and hydrophilic drugs. It can be engineered into nanoparticles, microcapsules, and hydrogels that provide controlled and sustained release, while its antibiofilm capacity reduces infection risks in implantable devices and wound dressings. This review consolidates current knowledge on sericin's extraction, biological functions, and emerging applications across tissue engineering, nanomedicine, and drug delivery. Unlike earlier reviews that primarily focused on either extraction chemistry or individual biomedical applications, the present review integrates extraction-dependent structure-function relationships with application-driven design strategies and highlights recent advances in sericin-based drug delivery and anti-infective platforms, thereby providing an updated and more translational perspective. It also highlights the challenges of improving mechanical stability, ensuring long-term biocompatibility, and advancing toward clinical translation. By bridging fundamental research and biomedical applications, sericin is presented as a sustainable and versatile protein with transformative potential in the development of next-generation biomaterials.
Keywords: Silk sericin; Biomaterials; Tissue engineering; Wound healing; Drug delivery; SILK PROTEIN SERICIN; REDUCING OXIDATIVE STRESS; POTENTIAL APPLICATIONS; ANTIOXIDANT ACTIVITY; PRECURSOR CELLS; IN-VITRO; SKIN; NANOPARTICLES; HYDROGELS; DELIVERY; Pharmacology & Pharmacy